Temporal dynamics in systems of qubits coupled to a bosonic mode (2021)
Through the numerical study of the properties of the temporal evolution of a state of a spin-boson system in the deep strong coupling regime, a rich structure of probability collapses and revivals is discovered. By analyzing the geometric properties of the trajectories of the Loschmidt amplitude associated to the problem, a connection between rotation directions and the probability collapses is made. The sources of this structure are then related to systems with a higher number of qubits, shedding light on the possible emergence of dynamic quantum phase transitions in these systems. Lastly, various perturbative approaches are presented to attempt a theoretical understanding for the emergence of such a structure.